Q. 84.6( 12 Votes )

Let us factorise

Answer :

Given, f(a)= 5a3 + 11a2 + 4a –2

In f(a) putting a=±1, ±2, ±3, we see for which value of a, f(a)=0


We observe that f(−1) = 0

From factor theorem, we can say, (a+1) is a factor of f(a)

5a3 + 11a2 + 4a –2 = 5a3 + 11a2 + 4a –2

= 5a3+5a2+6a2+6a−2a−2

= 5a2(a+1)+6a(a+1)−2(a+1)

= (a+1)(5a2+6a−2)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses